The Role of Financial Management Behavior in Mediating The Influence of Financial Technology and Financial Literacy on The Performance of Micro, Small, and Medium Enterprises (MSMEs) - Layinah; Maiyaliza (Rescollacom (Research Collaborations Community), 2026)
This study aims to analyze the influence of financial technology and financial literacy on the performance of MSMEs, with financial management behavior as a mediating variable. This study was conducted on 200 micro, small, and medium enterprises in the agriculture and fisheries sectors in Indramayu Regency. This study used quantitative techniques with Partial Least Squares–Structural Equation Modeling (PLS-SEM) analysis through SmartPLS 4 software. The results show that financial technology has a small and negative influence on financial management practices and organizational performance. Conversely, financial literacy has a substantial and beneficial influence on financial management practices and organizational performance. Furthermore, financial management behavior is proven to mediate the effect of financial literacy on company performance, while it does not mediate the effect of financial technology. The results show that the improvement in MSME performance is largely influenced by financial literacy and advanced financial management techniques, not by the use of financial technology, which is currently still limited.